Microfilaria Detection on Giemsa Blood Smears using Real-Time PCR - Paisal Paisal; Erli Haryati; Dwi Candra Arianti; Muhammad Rasyid Ridha; Annida Annida (Medical Laboratory Technology Journal, 2019)
Filariasis is an infectious disease caused by filarial worms, which found in many tropical and subtropical regions. In 2017, 12,677 cases of chronic filariasis were found in Indonesia, which 132 cases of them were from Central Kalimantan province. Data of Kapuas District Health Office shows 17 cases filariasis in 2015. Frequently, filariasis patients did not show any diseases symptoms, especially when the level of microfilariae in the blood is deficient. On the other hand, microscopic assay with Giemsa blood smears is still the gold standard to define filariasis. Thus, a false negative result may occur due to a low level of microfilariae in the blood. In this study, we develop a real-time PCR method, targeting the HhaI gene of filaria, to detect filarial worm from stored Giemsa blood taken from filariasis patients, in both dry and wet scraping methods. Our result shows that real-time PCR can detect Brugia malayi in all scraping samples, with Ct value from wet scraping sample tends to be higher than dry scraping. In conclusion, the real-time PCR method can be further used to define filariasis, especially in the condition when Giemsa smear blood cannot determine patient filariasis status.